Aflatoxin-specific monoclonal antibody selection for immunoaffinity column development - Ertekin, Özlem; Kaymak, Tuğrul; Pirinçci, Şerife Şeyda; Akçael, Esin; Öztürk, Selma (Biotechniques, 2019)
Antibodies are the basic components of immunoanalytical systems used for detection of a wide range of analytes. Although there are some ground rules for antibody selection, analyte- and assay-specific criteria are the ones that determine the ultimate success of the immunoassays. In this study, we introduced an effective antibody selection procedure for the development of immunoaffinity columns for aflatoxins. The designed scheme puts emphasis on solvent- and matrix-related characterization steps and was used to comparatively evaluate eight monoclonal antibodies. The selected antibody was tolerant to 40% methanol, 20% acetonitrile, 30% acetone and 40% ethanol and did not interact with corn, red pepper or hazelnut extracts. Immunoaffinity columns developed with the selected antibody were validated by 15 independent aflatoxin analysis laboratories.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Antibody selection; Immunoaffinity column; Matrix interference; Mycotoxin analysis; Solvent tolerance